Familial partial lipodystrophy linked to a novel peroxisome proliferator activator receptor ‐γ (PPARG) mutation, H449L: a comparison of people with this mutation and those with classic codon 482 Lamin A/C (LMNA) mutations. Issue 10 (5th February 2016) - Demir, T.; Onay, H.; Savage, D. B.; Temeloglu, E.; Uzum, A. K.; Kadioglu, P.; Altay, C.; Ozen, S.; Demir, L.; Cavdar, U.; Akinci, B.
Abstract: Aims: To describe the phenotype associated with a novel heterozygous missense PPARG mutation discovered in a Turkish family and to compare the fat distribution and metabolic characteristics of subjects with the peroxisome proliferator activator receptor ‐γ ( PPARG ) mutation with those of a cluster of patients with familial partial lipodystrophy with classic codon 482 Lamin A/C ( LMNA ) mutations. Methods: The study involved four subjects with familial partial lipodystrophy who had a novel PPARG mutation (H449L) and six subjects with classic codon 482 LMNA mutations (R482W). Results: Compared with subjects with LMNA R482W mutation, fat loss was generally less prominent in subjects with the PPARG H449L mutation. Partial fat loss was limited to the extremities, whilst truncal fat mass was preserved. The PPARG H449L mutation was associated with insulin resistance, hypertriglyceridaemia and non‐alcoholic fatty liver disease in all affected subjects, but the severity was variable. Three out of four mutation carriers had overt diabetes or impaired glucose tolerance. Pioglitazone therapy in these three individuals resulted in a modest improvement in their metabolic control, and regular menstrual cycles in the two female subjects. Conclusions: We suggest that relatively modest fat loss in patients with PPARG mutations may render the recognition of the syndrome more difficult in routine clinical practice. The PPARG H449L mutation is associated with insulin resistance and metabolic complications, but their severity is variable among the affected subjects. What's new?: In this study we compare the fat distribution and metabolic characteristics of subjects with familial partial lipodystrophy caused by a novel peroxisome proliferator activator receptor‐γ ( PPARG ) mutation, H449L, with those of a cluster of patients with familial partial lipodystrophy caused by classic codon 482 Lamin A/C ( LMNA ) mutations. PPARG H449L is associated with a slight fat loss that is limited to the extremities. PPARG H449L mutation is associated with insulin resistance in affected subjects, but the severity is variable.